Komunikasi Getok Tular : Revitalisasi Komunikasi dalam penanganan pandemi covid-19 (Komunikasi penanganan pandemi covid-19 dengan pendekatan Cultural Studies Stuart Hall) - Vildan Cresanda Hutama Putera (Jurnal Media dan Komunikasi Indonesia, 2022)
The paper encompass the literature review that discuss the revitalization of the communication by using Getok Tular communication technique in regards of covid-19 pandemic handling. The objective of this paper is to reflect any of relevant literature regarding revitalization of the communication for better handling of the covid-19 pandemic. The author uses literature review through journal, books and website to discover a relevant scope and discussions regarding revitalization of the communication in handling of covid-19 pandemic. The paper strives to describe covid-19 pandemic handling uses Getok Tular communication technique with Stuart Hall’s Cultural studies approach. The finding of the paper are; a) covid-19 pandemic handling needs a new approach in communication studies b) The two-way of communication is a new approach that can be applied to covid-19 pandemic c) Getok Tular communication technique is a communication studies by using cultural approach that can be an alternative of information dissemination for public in covid-19 pandemic handling.